Effect of dietary supplementation of humic substances on production performance and slaughter value of broiler chicken - Naď, Pavel; Marcin, Andrej; Bujňák, Lukáš; Skalická, Magdalena; Marcinčák, Slavomír (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
The effects of dietary supplementation with preparation of humic substances (HS) on production parameters were monitored in the experiment with the broiler chickens (n=90). The experimental groups were fed with the complete feed mixture for broiler chicken with the addition of 0.5% and 0.7% humic substances, respectively. The control group received the complete feed mixture without HS. The average live body weight of chickens was 2291.7 g in the control group and 2281.9 g (HS 0.5%) respectively 2326.6 g (HS 0.7%) in the experimental groups on day 35 of the experimental period. The average daily gain in the last week of the experiment was higher by 4.45 g in the group received 0.7% HS and lower by 2.38 g in the group received 0.5% HS compared to the control group. In the present study, the lower feed conversion ratio was observed in the control group (1.51 kg/kg) compared to experimental groups where feed conversion ratio was 1.53 (0.5% HS) and 1.63 (0.7% HS) kg/kg, respectively. Carcass weight of broilers at autopsy on day 37 in the experimental group (HS 0.7%) was significantly higher (P
Keywords: nutrition; humic substances; production; poultry